Loud or quiet quitting? The influence of work orientations on effort and turnover - Milena Nikolova (Global Labor Organization (GLO), 2024)
This study examines work orientations as a novel determinant influencing job search behaviors, quit intentions, and workplace effort, thereby integrating this concept into the field of labor economics. Work orientations, the intrinsic beliefs regarding the role of work in one's life, relate to viewing work as a paycheck, a career step, or a calling. Drawing on original, nationally representative Dutch data on work orientations, this paper reveals that those who view their work as a calling rather than a job are more committed to their roles, have lower quit intentions and are less likely to be job searching, and do not endorse 'quiet quitting'-the act of fulfilling only the minimum requirements to maintain employment. Conversely, individuals with career-centered work perspectives are more likely to consider leaving their jobs, engage actively in job searches, and show diminished work effort compared to those with a job orientation. However, this group is still unlikely to approve of quiet quitting in comparison to those who view work primarily as an income source. A key finding is that work orientations significantly predict quit intentions, job search behaviors, and effort levels-surpassing the predictive power of job satisfaction and perceived work meaningfulness. Specifically, work orientations account for about 40 % of the variation in quit intentions and job search behaviors. These insights suggest that work orientations could be a crucial, yet overlooked, factor in understanding employee behavior, challenging the conventional perspective of workers as simply income-driven and countering the notion of work as an inherent disutility.
Keywords: J24; J28; J81; M59; 330; work orientations; effort; quit intentions; job search